2020
DOI: 10.3390/plants9040452
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Localization and Antagonistic Function of NtPLC3 and PI4P 5-Kinases in the Subapical Plasma Membrane of Tobacco Pollen Tubes

Abstract: Polar tip growth of pollen tubes is regulated by the membrane phospholipid phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P 2 ), which localizes in a well-defined region of the subapical plasma membrane. How the PtdIns(4,5)P 2 region is maintained is currently unclear. In principle, the formation of PtdIns(4,5)P 2 by PI4P 5-kinases can be counteracted by phospholipase C (PLC), which hydrolyzes PtdIns(4,5)P 2 . Here, we show that fluorescence-tagged tobacco NtPLC3 displays a subapical plasma membrane distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Petunia PiPLC1 and tobacco NtPLC3 both localise to the plasma membrane in growing pollen tubes, in overlapping regions with their substrate PI(4,5)P 2 , although the protein localisation tends to elongate further towards the shank [ 185 , 239 ]. A similar co-localisation was observed for NtPLC3 and the Arabidopsis PI4P5Ks AtPI4P5K2 and 11 after transient expression in tobacco pollen tubes [ 240 ]. For petunia PiPLC1, image time series indicated that the PLC localisation extends towards the extreme apex in phases of reduced growth and is less apical in phases of rapid growth [ 185 ].…”
Section: Activity Of Phospholipase C Is the Main Degradation Routsupporting
confidence: 67%
See 3 more Smart Citations
“…Petunia PiPLC1 and tobacco NtPLC3 both localise to the plasma membrane in growing pollen tubes, in overlapping regions with their substrate PI(4,5)P 2 , although the protein localisation tends to elongate further towards the shank [ 185 , 239 ]. A similar co-localisation was observed for NtPLC3 and the Arabidopsis PI4P5Ks AtPI4P5K2 and 11 after transient expression in tobacco pollen tubes [ 240 ]. For petunia PiPLC1, image time series indicated that the PLC localisation extends towards the extreme apex in phases of reduced growth and is less apical in phases of rapid growth [ 185 ].…”
Section: Activity Of Phospholipase C Is the Main Degradation Routsupporting
confidence: 67%
“…In addition, so far, no Arabidopsis PI-PLC mutant was reported to be impaired in pollen tube growth. However, studies in other model systems highlighted PI-PLC importance to counterbalance PI4P5K-activity [ 185 , 239 , 240 ]. Petunia PiPLC1 and tobacco NtPLC3 both localise to the plasma membrane in growing pollen tubes, in overlapping regions with their substrate PI(4,5)P 2 , although the protein localisation tends to elongate further towards the shank [ 185 , 239 ].…”
Section: Activity Of Phospholipase C Is the Main Degradation Routmentioning
confidence: 99%
See 2 more Smart Citations
“…To further test whether the expression of StIPP would interfere with PtdIns(4,5)P 2 -dependent aspects of pollen tube growth in vivo, we assessed the impact of StIPP-YFP expression on pollen tube cell morphologies arising from the modulation of PtdIns (4,5)P 2 . Pollen tubes display characteristic cell morphologies upon overproduction of PtdIns(4,5)P 2 , which can easily be scored, including pollen tubes with branched or stunted tips (Ischebeck et al, 2008(Ischebeck et al, , 2010Stenzel et al, 2012;Hempel et al, 2017) or displaying tip swelling (Ischebeck et al, 2011;Stenzel et al, 2012Stenzel et al, , 2020. The range of pollen tube morphologies observed is represented in Fig 4(c), as indicated.…”
Section: Stipp Is Functional In Vivomentioning
confidence: 99%